Preserving Language, Resolving Conflict: Insights from Aceh and Patani - Saiful Akmal; Melly Masni; Anwar Koma; Ahmad Faizuddin; Nissa 'Ulfitri (Jurnal Ilmiah Peuradeun, 2026)
The preservation of local languages is critical in conflict-affected regions. Yet, a significant gap exists in comparative analysis exploring how divergent political settlements—post-conflict settlement versus ongoing conflict—shape language preservation strategies and outcomes. This study investigates how the de-securitization of language in Aceh, Indonesia, versus the ongoing language securitization in Patani, Thailand, produces fundamentally different strategies and challenges for revitalization. Employing a comparative case study methodology, we conducted semi-structured interviews with 20 stakeholders across both regions, performed non-participatory observation, and analyzed policy documents. Our findings reveal that Aceh’s formal recognition is undermined by implementation gaps, leading to institutional decay, while Patani’s grassroots efforts are constrained by state suspicion, fostering a model of community resilience. The study concludes that the state’s political decision to (de)securitize a minority language is the pivotal factor determining whether preservation efforts can achieve sustainable, institutionalized vitality beyond mere survival. This research offers a nuanced model for understanding the state’s central role in peacebuilding (SDG 16) through linguistic diversity, providing vital insights for language preservation strategies in other multilingual, conflict-affected regions.